MALAYSIAN ISLAMIC QUALITY MANAGEMENT SYSTEM MS 1900 FROM AN ISLAMIC PERSPECTIVE: AN IMPLEMENTATION MODEL - Basir, Siti Arni (Jurnal Syariah, 2011)
The purpose of this article is to provide a model that demonstrates the implementation process of Malaysian Islamic Quality Management System, MS 1900. MS 1900 is a structured system that assists organizations to deliver products and services that meet customers’ requirements, comply with regulatory requirements as well as with the requirements of Shariah. The system was launched in 2005 with its ultimate aim to fill in the gap according to the ISO 9001 standard in relation to the Islamic perspective. A wide range of literature was reviewed, with particular focus on the Quality Management Standard ISO 9001 and Malaysian Islamic Quality Management Standard MS 1900. The model that is developed consists of three components, namely; the implementation steps of ISO 9001, Shariah elements in MS 1900 requirements and MS 1900 principles. The article concludes that shariah elements were synchronized into the existing ISO 9001 in order to establish the first ever Islamic quality management system – MS 1900. MS 1900 is a holistic Islamic quality management system, which incorporates its principles and requirements. The MS 1900 not only helps organizations improve their management system, but also enables organizations to practice management systems in accordance with Shariah and Islamic obligations. The model proposed should be followed by managers so that MS 1900 can be implemented effectively. This is crucial to ensure that the implementation of MS 1900 will bring benefit to organizations. This article makes a contribution to the literature on Islamic quality management systems. It is believed to be one of a few studies that investigate the issue of quality management systems in Islam. This article also highlights areas for further research for academics and professionals alike.